Analisis Surfaktan NaLs dari Ampas Tebu dan Sabut Kelapa Terhadap Peningkatan Oil Recovery pada Skala Laboratorium - Hasugian, Ritchad Steven Partogi; Garanta, Rendy Prasetiyo (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
In the oil and gas industry, EOR—particularly the use of surfactants—plays a strategic role in increasing oil recovery from oil and gas wells in Indonesia. Conventional oil recovery faces serious challenges in the form of declining reservoir pressure and permeability over time. Enhanced Oil Recovery (EOR) is an advanced oil recovery method employed when primary and secondary recovery methods are no longer effective. This study aims to analyze the effect of sodium lignosulfonate (NaLS) surfactants derived from sugarcane bagasse and coconut husks on oil recovery enhancement, as indicated by a decrease in interfacial tension, with surfactant concentrations of 0.5%, 1.0%, 1.5%, and 2.0%, with salinity variations ranging from 10,000 ppm to 40,000 ppm. The results of this study demonstrated the ability to reduce the interfacial tension (IFT) between oil and water, though this effect was limited to a concentration of 1.0% for sugarcane bagasse and 1.5% for coconut husk, with the resulting emulsion having the same value of 0.4 cm.